PERSEPSI AUDITOR EKSTERNAL TERHADAP DIGITALISASI AUDIT MELALUI TEKNIK AUDIT BERBANTUAN KOMPUTER - Octavia Lhaksmi Pramudyastuti; Rani, Utpala; Suryatimur, Kartika Pradana; Wahyuningtiyas, Titania Nur (Politeknik Negeri Ambon, 2022)
The Covid-19 pandemic has accelerated the digitalization era in Indonesia, including in the field of audit services. Various Public Accounting Firms have started to implement audit digitization through Computer Assisted Audit Techniques (TABK). Digitization of this audit in addition to bringing quite a lot of benefits, but also creates a variety of responses to its use, especially from external auditors. This study aims to identify how the external auditor's perspective on audit digitization through Computer Assisted Auditing Techniques. This research is a qualitative descriptive study that explains the results of a data set to find out how the perceptions, implementation, and constraints on the digitalization of audits through TABK. Through surveys and interviews to respondents, it was found that the external auditor's perception is determined by several things, including: social influence, workplace or supervisor, and facilities in audit software. Currently, there is a special TABK created by the Financial Profession Development Center - Ministry of Finance and Indonesian Institute of Certified Public Accountants, namely ATLAS (Audit Tool and Linked Archive System). ATLAS is a form of digitizing auditing in Indonesia, but there are still some weaknesses in its operation. Continuous system improvement is needed to improve the performance of the ATLAS system.